Maintaining intimacy during the COVID‐19 pandemic. Issue 4 (20th May 2022) - Wolf, Tabea; Nusser, Lisa
Abstract: The present study investigated whether autobiographical memories serve to maintain feelings of intimacy in times of social isolation that result from the restrictions related to the COVID‐19 pandemic. Data came from 104 young and older adults who reported three important and three social memories, that is, memories about someone the participants were unable to meet because of the pandemic‐related restrictions. Our findings support that social memories more frequently serve intimacy functions than important memories do, and this difference is more pronounced for older compared to young adults. Moreover, social loneliness is associated with less frequent use of important memories for intimacy functions, whereas emotional loneliness shows a positive association. Results are discussed in terms of what type of memories can be used to maintain intimacy feelings across age groups and regarding qualitative and quantitative aspects of loneliness that differently predict the use of memories for intimacy functions.